Phylogeny of Phyllachora species on bamboo and P. cephalostachyi sp. nov. from China - Li, Xiao-Ling; Yu, Hai-Ying; Luo, Xi; Wu, Hao; Zhao, Chun-Yan; Promputtha, Itthayakorn; Sun, Da-Feng (Phytotaxa, 2021)
Thirty-seven Phyllachora specimens were collected in China and examined for morphological characteristics. A molecular phylogenetic analysis based on a combined sequence dataset of ITS and LSU was also undertaken. Phyllachora cephalostachyi sp. nov. on Cephalostachyum pergracile is described based on its distinct phylogenetic relationships and a comparison of its morphological characteristics with known Phyllachora species on bamboo. Our results indicate a high species diversity of Phyllachora on bamboo in China. A full description and colour photographs of micro-characters are provided for the new species. A phylogenetic tree to show placement of the new species, and a table to compare morphology of the Phyllachora species reported on bamboo are also provided.